2011
DOI: 10.1007/s10554-011-9984-1
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of F18-FDG-PET/CT in the diagnosis of endocarditis: preliminary evidence from a review of the literature

Abstract: Infective endocarditis (IE) is a particular disease which presents with a variety of clinical, aetiological forms and is lethal if not aggressively treated with antibiotics alone or in combination with surgery. This review tries to analyse the possible role of F18-FDG-PET/CT in the diagnosis of IE based on the state of art in literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 58 publications
0
14
0
4
Order By: Relevance
“…The role of FDG-PET/CT in the diagnosis of valvular endocarditis has been suggested by several small studies and sporadic case reports; however, with some controversy [15][16][17][18][19][20][21]. This controversy most probably derives from the lack of a standardized protocol for myocardium imaging with FDG-PET/CT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of FDG-PET/CT in the diagnosis of valvular endocarditis has been suggested by several small studies and sporadic case reports; however, with some controversy [15][16][17][18][19][20][21]. This controversy most probably derives from the lack of a standardized protocol for myocardium imaging with FDG-PET/CT.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated the role of FDG-PET/CT in detecting infections of vascular prostheses [8][9][10] and implantable pacemakers/ defibrillators [11][12][13][14]. Furthermore, an important role of FDG-PET/CT in the diagnosis of IE has been proposed by several recent publications [15][16][17][18][19][20][21]. Few data regarding the diagnosis of ECC by FDG-PET/CT exist [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, PET/CT may be proposed to improve spatial resolution. In this regard, preliminary data have demonstrated significant uptake of 18 F-FDG both in infected endocardial vegetations and at metastatic sites of infection (27)(28)(29)(30). However, 18 F-FDG uptake is observed in a variety of benign and malignant conditions such as inflammation or tumors (31), thus reducing its specificity.…”
Section: Discussionmentioning
confidence: 99%
“…En la actualidad numerosos estudios de investigaci贸n van dirigidos a asignar al PET un nuevo enfoque y una nueva utilidad diagn贸stica en el campo de la patolog铆a infecciosa e inflamatoria, convirti茅ndose en el nuevo paradigma en patolog铆as como la endocarditis infecciosa, vasculitis de grandes vasos, enfermedad inflamatoria intestinal, infecci贸n de pr贸tesis vasculares, fiebre de origen desconocido u osteomielitis cr贸nica, entre otros [13][14][15][16][17][18] .…”
Section: Discussionunclassified